Geomagnetic Excursions Recorded in North Atlantic IODP Expedition 395C Sites U1555 and U1563 - Anita Di Chiara; Sara Satolli; Sarah A. Friedman; Deepa Dwyer; Gary D. Acton; Tom Dunkley Jones; Boris Theofanis Karatsolis; Paul N. Pearson; Takuma Suzuki; Sevasti Modestou; Suzanne O'Connell; Halima Ibrahim; et al. (Geochemistry, Geophysics, Geosystems)
Abstract By studying deep‐sea drilled records from the North Atlantic Ocean, several magnetic instabilities of short duration, such as the Iceland Basin (188 ka), the Björn (1,255 ka) and the Gardar (1,460 ka) excursions, were discovered. These records have contributed to our understanding of Earth's magnetic field and are the foundation of the Geomagnetic Instability Time Scale (GITS) in the Quaternary. Here, we present the magnetostratigraphy from Sites U1555 (0 to ∼2.7 Ma) and U1563 (0 to ∼5.2 Ma) drilled during the International Ocean Discovery Program Expedition 395C on the eastern side of the modern Mid‐Atlantic Ridge (∼60°N, 20–30°W). Shipboard paleomagnetic and microfossil data provided a preliminary age model, extending the regional record to 3.4 Ma. The Virtual Geomagnetic Pole latitudes from archive halves, corroborated with data from discrete samples, were used to build a high‐resolution magnetostratigraphy, which contained the expected Brunhes and Matuyama Chrons and their respective Subchrons. We also identified most of the magnetic events reported in the GITS, including the less well‐documented ones, such as Osaka, Kamitzukara, Huckleberry Ridge, Reunion, Gardar, Halawa and L4 events. The high‐resolution magnetostratigraphy from Sites U1555 and U1563 is compared with two previous legacy sites and contributes toward an increasingly robust GITS, expanding its use as a correlation and dating tool.